Pemanfaatan Mesin Pencacah Dalam Meningkatan Pakan Silase Ternak Domba Ukm Barokah Farm - Edy Suryono; Bambang Margono; Emanuel Budi Raharjo; Alwan Kusuma Romadhoni; Wisnu Wahyu Bakti (Pusat Penelitian dan Pengabdian Masyarakat, 2026)
Barokah Farm is a sheep farming business in Barukan Village, Manisrenggo District, Klaten Regency, that uses a silage-based feed bank system to ensure year-round feed availability. The problem partners face is that forage shredding is still done manually, which takes a long time, has low production capacity, and cannot meet silage needs sustainably. This community service program aims to increase silage production efficiency by implementing a feed shredder and adding fermentation facilities. The implementation method includes field surveys, problem identification, design and construction of the shredding machine, tool testing, training, and assistance in utilizing the tool for partners. The machine used is a 3 HP diesel engine with three cutting blades and a working capacity of 83.3 kg/hour. The results of the activity showed that using the shredding machine can increase the production capacity of silage raw materials by up to 3 times compared to the manual method. Partners can produce 3 barrels of silage in approximately 60 minutes, resulting in more uniform shredded sizes and better fermentation. The resulting silage has good physical characteristics, including a brownish color, a fresh, fermented aroma, and high acceptance by sheep. This program has successfully increased productivity, work efficiency, and capacity for livestock feed management at the Barokah Farm SME.